Eradication of hepatitis C virus infection in kidney transplant recipients using direct‐acting antiviral therapy: Qatar experience - Mohamad M. Alkadi (14778640) (2020)
Introduction Hepatitis C virus (HCV) infection has detrimental effects on patient and graft survival after kidney transplantation. In the pre-direct-acting antiviral (DAA) era, treatment of HCV infection was associated with low response rates, poor tolerance, and increased risk of allograft rejection. However, DAAs have revolutionized HCV treatment. The aims of this study were to determine the impact of DAA on the sustained virologic response (SVR), renal function, and calcineurin inhibitor (CNI) levels and assess the tolerability to treatment in kidney transplant recipients with HCV infection in Qatar. Methods This retrospective study included the medical records of all kidney transplant recipients with confirmed HCV infection before January 1, 2020. All data were obtained from the patients’ electronic medical records; these included patient demographics; virologic responses to treatment; serum creatinine levels during treatment; urine protein to creatinine ratios and CNI levels before, during, and after treatment; and side effects related to DAA therapy. Results A total of 27 kidney transplant recipients with HCV were identified, 23 of whom received DAA therapy. The length of treatment ranged from 12 to 24 weeks, and 52% of patients had HCV genotype 1 infection. The median log10 HCV RNA was 6.6 copies per milliliter. None of the patients had liver cirrhosis, and all of them achieved SVR. There was no statistically significant difference in the glomerular filtration rate before, during, and after treatment. Most patients had stable CNI trough levels during treatment and did not require dose adjustment. Conclusions HCV infection was successfully eradicated by DAA therapy in kidney transplant recipients, with a 100% SVR rate. Moreover, DAA therapy was well-tolerated, and kidney function remained stable without an increased risk of rejection. These results are expected to drive the eradication of hepatitis C from the entire country. Other Information Published in: Immunity, Inflammation and Disease License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1002/iid3.386